Optimization of Human Resources in the Housekeeping Department Case Study of The Alana Hotel Malang - Shanhaji Shanhaji; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the factors that influence performance and service quality in the housekeeping department and provide strategic recommendations for optimizing human resource management. The main focus of the study includes low work motivation due to inadequate incentives, limited relevant training, high turnover rates, and ineffective leadership at the supervisor level. This analysis is based on theories of work motivation, training and development, and leadership theories. Data were collected through three-month observations in three-star hotels in Semarang, in-depth interviews with 15 housekeeping employees and five supervisors, and analysis of documentation related to HR policies. This study uses a descriptive qualitative approach to understand the impact of these factors on employee performance. The results showed that the lack of incentives has an impact on low work motivation, with 70% of respondents stating that current compensation does not encourage optimal performance. In addition, irrelevant training hinders skill development, while high turnoverwith an average employee turnover of 30% per yeardisrupts team stability. Ineffective leadership also worsens working conditions and reduces productivity. As a solution, the study recommends increasing the training budget, implementing a performance-based reward system, improving managerial skills for supervisors, more effective recruitment strategies during the holiday season, and implementing more consistent and standardized standard operating procedures (SOPs). Implementing these strategies is expected to increase employee motivation, reduce turnover, and improve the overall quality of housekeeping services.